Parallel Spinal Pathways for Transmitting Reflexive and Affective Dimensions of Nocifensive Behaviors Evoked by Selective Activation of the Mas-Related G Protein-Coupled Receptor D-Positive and Transient Receptor Potential Vanilloid 1-Positive Subsets of Nociceptors - Wang, Liang-Biao; Su, Xiao-Jing; Wu, Qiao-Feng; Xu, Xiang; Wang, Xin-Yue; Chen, Mo; Ye, Jia-Reng; Maimaitiabula, Abasi; Liu, Xiao-Qing; Sun, Wen; Zhang, Yan (Frontiers in Cellular Neuroscience, 2022)
The high incidence of treatment-resistant pain calls for the urgent preclinical translation of new analgesics. Understanding the behavioral readout of pain in animals is crucial for efficacy evaluation when developing novel analgesics. Mas-related G protein-coupled receptor D-positive (Mrgprd+) and transient receptor potential vanilloid 1-positive (TRPV1+) sensory neurons are two major non-overlapping subpopulations of C-fiber nociceptors. Their activation has been reported to provoke diverse nocifensive behaviors. However, what kind of behavior reliably represents subjectively conscious pain perception needs to be revisited. Here, we generated transgenic mice in which Mrgprd+ or TRPV1+ sensory neurons specifically express channelrhodopsin-2 (ChR2). Under physiological conditions, optogenetic activation of hindpaw Mrgprd+ afferents evoked reflexive behaviors (lifting, etc.), but failed to produce aversion. In contrast, TRPV1+ afferents activation evoked marked reflexive behaviors and affective responses (licking, etc.), as well as robust aversion. Under neuropathic pain conditions induced by spared nerve injury (SNI), affective behaviors and avoidance can be elicited by Mrgprd+ afferents excitation. Mechanistically, spinal cord-lateral parabrachial nucleus (lPBN) projecting neurons in superficial layers (lamina I-IIo) were activated by TRPV1+ nociceptors in naïve conditions or by Mrgprd+ nociceptors after SNI, whereas only deep spinal cord neurons were activated by Mrgprd+ nociceptors in naïve conditions. Moreover, the excitatory inputs from Mrgprd+ afferents to neurons within inner lamina II (IIi) are partially gated under normal conditions. Altogether, we conclude that optogenetic activation of the adult Mrgprd+ nociceptors drives non-pain-like reflexive behaviors via the deep spinal cord pathway under physiological conditions and drives pain-like affective behaviors via superficial spinal cord pathway under pathological conditions. The distinct spinal pathway transmitting different forms of nocifensive behaviors provides different therapeutic targets. Moreover, this study appeals to the rational evaluation of preclinical analgesic efficacy by using comprehensive and suitable behavioral assays, as well as by assessing neural activity in the two distinct pathways.